Snake Species and Their Habitat Preferences on Marsegu Island, West Seram, Maluku, Indonesia - Samangun, Christmas; Eddy, La; Leimena, Handy Erwin Pier (RUMPHIUS, 2025)
Maluku, an archipelagic region, has unique ecological features that support a high level of biodiversity. One such island in this region is Marsegu Island, located in the Western Seram Regency, which is recognised as a nature reserve and serves as a natural habitat for several species of snakes. This study identifies snake species and analyses habitat preferences on Marsegu Island. Data were collected using the Visual Encounter Survey (VES) method. A total of six snake species from four families were recorded, with Colubridae being the most dominant. Species showed distinct habitat preferences: Xenopeltis unicolor was often found under decaying wood in mangrove areas, while Ahaetulla prasina was associated with Cerbera manghas trees. Larger species, such as Malayopython reticulatus, were found in coral rubble, while Cerberus schneiderii preferred semi-aquatic habitats in mangrove mud. The results suggest that the distribution of snakes on Marsegu Island is strongly influenced by morphological and behavioral adaptations to specific habitat types. This study provides new ecological insights into snake species in mangrove ecosystems and highlights the critical role of habitat conservation in maintaining biodiversity on Marsegu Island.